Post-COVID-19 Adaptations; the Shifts Towards Online Learning, Hybrid Course Delivery and the Implications for Biosciences Courses in the Higher Education Setting - Bashir, Amreen; Bashir, Shahreen; Rana, Karan; Lambert, Peter; Vernallis, Ann (Frontiers in Education, 2021)
The Covid-19 pandemic has created challenges and caused disruption across the Higher Education sector; university campuses closed, and face-to-face teaching and assessment shifted to an online format. Learning from our students’ experience during this period will help us shape future hybrid delivery so that it best fits Bioscience students. This pedagogical study explored Aston University’s Bioscience students’ experiences of studying from home, and the impact of the lockdown on mental wellbeing and quality of life. 151 students completed an online survey during August 2020, which included open and closed questions. Analysis of survey data revealed that a majority of students reported positive experiences of online open-book assessments and most would welcome this format in the future. The majority of students faced no technical issues, predominantly stating that they also had good internet connectivity. Shifting to remote learning and online classrooms uncovered conflicting preferences; despite wanting more interactive lectures, only half of the students were comfortable interacting using video cameras. Free text responses provided an insight into how some students reported an inadequate home working space/environment and lacked necessary items such as a desk, highlighting how remote working may intensify social and digital inequality - particularly for students from more deprived households. Wider detrimental experiences of lockdown included dissatisfaction with access to healthcare, decreased concentration, sleeping difficulties and a decline in mental wellbeing. Education strategies going forward will need to address the mental health needs of students who have suffered during the pandemic. Our university, amongst others, is embracing hybrid course delivery, which could offer a solution to ensuring Bioscience students receive hands-on laboratory experience and face-to-face contact to remain motivated and benefit from the on-campus facilities and support, whilst allowing students some of the flexibility afforded by remote study. In the current competitive higher education market where student retention is key, it is important to consider student demographics and digital equity to ensure an appropriate approach is applied to cater for all students.